Predesign of Biphenyl Chemical Factory from Benzene with Capacity of 10.000 Ton Per Year - Roman Robiati (Natural Sciences Engineering and Technology Journal, 2021)
Biphenyl is one of the most important supporting materials needed in the chemical industry as an intermediate. This study aimed to describe the technical review of the biphenyl plant design to be built in Gresik, East Java. The predesign process of the biphenyl plant consists of the analysis of the location of the factory, analysis of the benzene process, and analysis of utility calculations. The factory is designed to operate continuously for 330 days, 24 hours per day, and requires 214 employees. The manufacture of biphenyl begins by reacting benzene in a pipe flow reactor (R-01) at a reactor temperature of 377ºC and a pressure of 2 atm. Economic analysis shows that the value of ROI before tax is 50.38%, and the value of ROI after tax is 32.75%. POT before tax is 1.65 years, and POT after tax is 2.34 years. The BEP value is 43.11%, and the SDP value is 23.75%. The interest rate in DCF for 10 years averages 19%. In conclusion, a biphenyl plant from benzene with a capacity of 10,000 tons/year is worth considering from a technical and economic point of view.